A New Wave in the Modern History of the Abuse Crisis in the Catholic Church: Literature Overview, 2018–2020 - Faggioli, Massimo 1970-; O'Reilly-Gindhart, Mary Catherine (2021)
This article focuses on the theological discourse on the abuse crisis in the wider context of the institutional response to the scandal and argues for theological research having a role less subordinated to legal and canonical considerations. The year 2018 marked the beginning of a new phase in the history of the abuse crisis in the Catholic Church. This article analyzes an extensive list of publications and resources (2018–2020) across all continents, even though focus is here primarily on the US, Europe, and Anglophone regions. This aspires to be the first installment of literature reviews, beginning a much larger discussion, contributing to the creation of a global, interdisciplinary network of connections in the field of the research on theology and the abuse crisis in the Catholic Church.
Keywords: Survivors; spiritual abuse; sex abuse; Prevention; abuse of power; abuse crisis